COURSES IN LMS MOODLE - A MEANS OF THE E-LEARNING IN MATHEMATICS - GREGÁŇOVÁ, Radomíra (Trends in education, 2009)
The teaching of mathematics is interconnected with the application of information technologies. The study materials are created in the form of electronic documents or on-line courses. At the Slovak University of Agriculture in Nitra the practical realization of this kind of educational ways and creation study materials is supported by LMS Moodle. In the paper we present learning management system Moodle and the possibilities of its integration into the mathematical subjects taught at the Slovak University of Agriculture in Nitra.
Keywords: teaching of mathematics; e-learning; electronic study materials; LMS Moodle.